Chapter 1 Introduction - James, Toby S. (Routledge Studies in Elections, Democracy and Autocracy, 2020)
In the immediate aftermath of the 2007 Kenyan Presidential election, the country entered into a political, economic and humanitarian crisis. Post-election violence erupted leading to estimates of over 1,000 people being killed by police, criminal gangs and militia groups, and 660,000 displacements, as opponents of President Mwai Kibaki alleged electoral manipulation (CBS News 2008; Kenny 2019). Tensions were deeply rooted in Kenya's political history.